Selection Strategy for Site-Directed Mutagenesis Based on Altered β-Lactamase Specificity. (June 1998) - Andrews, Christine A.; Lesley, Scott A.
Conventional approaches to oligonucleotide-directed mutagenesis rely upon the application of a selection strategy to maximize mutagenesis efficiencies. We have developed a mutagenesis procedure that incorporates a novel antibiotic resistance for selection. The selection involves altering the substrate specificity of TEM-1 β-lactamase, the enzyme responsible for bacterial resistance to β-lactam antibiotics such as ampicillin. The gene encoding β-lactamase is commonly found on cloning and shuttle vectors used in molecular biology. Amino acid substitutions in several active site residues of β-lactamase result in increased hydrolytic activity against extended-spectrum penicillins and cephalosporins. This increased activity confers a novel resistance specific to the mutant and thus provides the basis of the selection strategy. We describe a simple and efficient mutagenesis procedure and its application to creating a range of oligonucleotide-directed mutants.